Peridural com ropivacaina a 1%: Experiencia com volume proporcional a estatura - Ganem, Eliana Marisa [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Takata, I. H. [UNESP]; Achoa, R. V. [UNESP]; D'Angelo, S. M. [UNESP]; Zacchi, B. [UNESP] (My University, 1998)
Background and Objectives - Ropivacaine - a local amino amide anesthetic agent - is a plain S enantiomer which makes it a potent and low toxicity drug. The aim of our study was to evaluate 1% ropivacaine for epidural block in lower doses than those described in the literature. Methods - Thirty-eight patients, physical status ASA I and II, aged 15 to 70 years, weighing 50 to 100 kg were selected. Premedication consisted of 15 mg oral midazolam given 60 min before anesthesia induction. In the OR, after standard monitoring a catheter was inserted intravenously to administer 10 ml.kg-1 Ringers lactate solution. Epidural puncture was performed with the patient in the sitting position and 1% ropivacaine was administered in a volume corresponding to 10% of patient's height in centimeters. With the patient in the supine position, motor blockade intensity, temperature sensitivity and sensory block extension at 1, 3, 5, 7, 10, 15, 20, 30 minutes after drug injection were evaluated. Blood pressure, heart rate and adverse side effects during the course of anesthesia and in the post-anesthetic period were also observed. In the recovery room patients were followed-up until motor blockade intensity temperature sensitivity and sensory block had returned to level L2. Results - Mean values were 41.4 years of age, 68.8 kg of body weight and 165 cm height. Upper thermal blockade level was T4 and upper sensory block level was T6. Most patients showed motor block level 1 (Bromage scale) after 30 minutes of observation. Motor block mean duration was 254 minutes and temperature sensitivity 426 minutes. Only three patients had complications: two cases of hypotension and one of bradycardia. Conclusions - In the volumes used in this study, ropivacaine produced adequate analgesia and a less intense lower limb motor block which, however, was sufficient to allow for surgical procedures with low incidence of side-effects.
Epidural anesthesia with 1% ropivacaine: Experience with volume proportional to height
Keywords: Anesthetic techniques: regional, epidural; Anesthetics: local, ropivacaine; local anesthetic agent; midazolam; ropivacaine; adolescent; adult; aged; blood pressure; bradycardia; clinical article; epidural anesthesia; heart rate; human; hypotension; intravenous drug administration; nerve block; oral drug administration; premedication; supine position; temperature sensitivity